Communication Difficulties Due to Lexical Differences in Adjectives: A Comparative Study of Yousafzai and Banuchi Dialects - Sahrish; Dr. Muhammad Imran; Tehneyat Shakoor, (Dialogue Social Science Review (DSSR), 2025)
This study aims to present the vocabulary differences between Yousafzai and Banuchi dialects of Pashto language. As there are different words in both dialects which are used for the same things due to which speakers of both dialects face communication difficulties. The objective of the current study is to find out communication difficulties in both dialects in the use of adjectives through a comparative study. The researcher has conducted focused group interviews and used audio recording as a tool to collect data from the respondents. The data was collected from both male and female to fulfil the integrity of the research. The data was analyzed and presented in tabulated and graphical form. The results of the research illustrate the level of lexical differences between both dialects. It is expected that the findings of this research will present a set of general ideas for the solution of communication difficulties among Pashto speakers of Khyber Pakhtunkhwa.